Payload swing control of a tower crane using a neural network–based input shaper - Fasih S.M.; Mohamed Z.; Husain A.R.; Ramli L.; Abdullahi A.M.; Anjum W. (SAGE Publications Ltd, 2024)
Indexed by WOS/SCOPUS